Relationship Between Emotional Intelligence, Work Attitude & Outcomes: Examination of Indian Middle-Managerial Level Employees - Sinha, Chandranshu; Kumar, Himani (Journal of Organizational Psychology, 2016)
This study is an attempt to assess the impact of emotional intelligence on middle level managers in Indian organizations. The study examines the extent to which middle level managers with high emotional intelligence are capable of developing positive work attitudes and outcomes. The results indicate that emotional intelligence had significant relationship with work attitudes and work outcomes which also impacted work family conflict, job involvement and job performance in the Indian context. However, career commitment, organisational commitment and job satisfaction was found to have no impact of high/low emotional intelligence possessed by employees in Indian cultural context.